Kontroversi Hukum Shalat Gaib: Analisis Fiqh Al-Hadith - M. Jakfar, Tarmizi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
Among the types of prayers performed by Muslims on the dead body is occult prayer, which is blaming the body of his fellow Muslim brother who died, but the body is not in front of the person performing the funeral prayer, but is elsewhere. Regarding the observance of occult prayers, there is disagreement among scholars. Some are restrictive and some forbid and there are also scholars who view the Sunnah in certain circumstances, not in others. This difference arises due to differences in the way the scholars of the madhab take religious law from the hadith text. In this study, the author uses a type of library research and this type of research is comparative descriptive with the fiqh al-hadith approach. The crux of the problem in this article is: first, what is the quality of the hadiths about occult prayers. Second, How is the quality of the hadiths related to occult prayers with the understanding of madhab scholars. Imam al-Shafi'i and one of Imam Ahmad's opinions consider the occult funeral prayer to be absolutely solemnized, based on the hadith of Najasyi. According to them, this hadith is a common proposition. Imam Hanafi and Imam Malik said it was forbidden, because the practice of praying the occult corpse of the Prophet (saw) over Najasyi was a specialty for the Prophet (saw) that should not be followed by the people, as for the practice of praying the Prophet over Najasyi, because Allah had raised Najasyi before the Prophet (saw). While other scholars such as Ibn Taymiyah, Abdurrahman 'Ali Sa'di, Shaykh Ibn Baz and others, argue that the prayer of the occult corpse is prescribed under certain conditions only, not in other conditions. This condition is if the corpse has great priority and contribution to the people, as well as those who have not been prayed the body.Abstrak: Di antara jenis shalat yang dilakukan oleh kaum muslimin terhadap jenazah adalah shalat gaib, yakni menyalatkan jenazah saudaranya sesama muslim yang wafat, tetapi jenazahnya tidak berada di depan orang yang melakukan shalat jenazah itu, melainkan berada di tempat lain. Mengenai disyariatkannya shalat gaib terdapat perselisihan di kalangan ulama. Ada yang menyunahkan dan ada pula yang mengharamkan dan ada juga ulama yang memandang sunnah dalam keadaan tertentu, tidak dalam keadaan yang lain. Perbedaan ini timbul dikarenakan adanya perbedaan cara para ulama mazhab dalam pengambilan hukum agama dari teks hadis. Dalam penelitian ini, penulis menggunakan jenis penelitian kajian kepustakaan (library research) dan tipe penelitian ini adalah deskriptif komparatif dengan pendekatan fiqh al-hadith. Inti permasalahan dalam artikel ini adalah: pertama, bagaimana kualitas hadis-hadis tentang shalat gaib. Kedua, Bagaimana keterkaitan kualitas hadis-hadis shalat gaib dengan pemahaman ulama mazhab. Imam al-Syafi’i dan salah satu pendapat Imam Ahmad menilai shalat jenazah gaib disyariatkan secara mutlak, di dasarkan pada hadis Najasyi. Menurut mereka hadis tersebut merupakan dalil yang umum. Imam Hanafi dan Imam Malik mengatakan diharamkan, karena praktek shalat jenazah gaib Nabi saw. atas Najasyi merupakan kekhususan bagi Nabi saw. yang tidak boleh diikuti oleh umat, adapun praktek shalat Nabi atas Najasyi, karena Allah telah mengangkat Najasyi di hadapan Nabi saw. Sedangkan ulama lain seperti Ibn Taymiyah, Abdurrahman ‘Ali Sa’di, Syaikh Ibn Baz dan yang lainnya, berpendapat shalat jenazah gaib disyariatkan dalam kondisi tertentu saja, tidak pada kondisi yang lain. Kondisi tersebut adalah jika jenazah memiliki keutamaan dan andil besar untuk umat, serta yang belum dishalatkan jenazah.